UNDERSTANDING ACTIVE AND PASSIVE VOICE: CHALLENGES AND SOLUTIONS FOR ENGLISH LEARNERS - Sari, Rani Puspa; Pangaribuan, Jeyola Josevine (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This study explores English learners' comprehension of active and passive voice usage, the difficulties encountered, and potential solutions. Through a case study involving high school students, it was found that many students struggle with correctly distinguishing and applying these two grammatical forms. The proposed solutions include contextual teaching methods and leveraging technology in instruction. The research aims to contribute to the enhancement of English grammar education and offer practical recommendations for educators to improve students' grammatical skills